2018
DOI: 10.1002/wene.323
|View full text |Cite
|
Sign up to set email alerts
|

Ex post evaluation of energy efficiency programs: Case study of Czech Green Investment Scheme

Abstract: A significant amount of financing has been available for improvements in energy efficiency in buildings in recent years. However, careful evaluation of the real impacts of the programs is still inadequate. The paper provides an insight into the relationship between the expected outcomes and the actual results of an energy efficiency program. It does so on a case example of one of the most significant energy efficiency and renewable energy sources programs in Central Europe, the Green Savings Programme. In tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Although it is impossible to observe the physical quantities that define 'efficiency' in the engineering sense, by building from the disaggregated data and incorporating the changes in other explanatory factors, the measures of intensity more closely approximate the changes in the underlying efficiency of energy use (Xu and Ang 2014;Goh and Ang 2018). Differing from ex ante engineering estimates, these ex post estimates of energy savings account for potential rebound effects and other behavioural responses or implementation challenges that typically reduce the expected energy savings from energy efficiency improvements (Sorrell 2007;Fowlie et al 2018;Gillingham et al 2018;Valentová et al 2018).…”
Section: Methodsmentioning
confidence: 99%
“…Although it is impossible to observe the physical quantities that define 'efficiency' in the engineering sense, by building from the disaggregated data and incorporating the changes in other explanatory factors, the measures of intensity more closely approximate the changes in the underlying efficiency of energy use (Xu and Ang 2014;Goh and Ang 2018). Differing from ex ante engineering estimates, these ex post estimates of energy savings account for potential rebound effects and other behavioural responses or implementation challenges that typically reduce the expected energy savings from energy efficiency improvements (Sorrell 2007;Fowlie et al 2018;Gillingham et al 2018;Valentová et al 2018).…”
Section: Methodsmentioning
confidence: 99%
“…emissions reductions from a Czech green investment scheme were 25% lower than expected (Valentová et al, 2019); (ii) environmental regulations do not automatically lead to desired impacts in reduced environmental impacts (Knill et al, 2012); (iii) residential loft and cavity wall insulation measures were found to have reduced fuel use by as little as a third of predicted savings (Wade and Eyre, 2015); two UK competitions for early stage CCS technology development funds were withdrawn without winners between 2007 and 2015; the Green Deal scheme of 2013 (Mallaburn and Eyre, 2012) was cancelled early due to poor take-up i ..…”
Section: The Challengementioning
confidence: 74%
“…However, the energy savings that are realized in practice due to energy efficiency improvements generally 3 fall short of these ex ante engineering estimates. Several studies indicate that engineering calculations may be prone to overstating the energy savings from energy efficiency investments because they cannot account for rebound effects and other behavioral adjustments or implementation challenges, leading to less energy savings than would be expected (Gillingham et al 2018;Valentová et al 2018;Gillingham and Palmer 2014;Sorrell 2007). In addition, the principle of 'additionality' on which these calculations are based on -counting only the energy savings that are effectively additional as a consequence of specific policy interventions -raise further concerns regarding their reliability due to the difficulties of avoiding double-counting issues (e.g., actions that are counted twice under the same measure or actions receiving incentives from two different measures -Labanca and Bertoldi 2016), and potential complementarities or trade-offs with other national, regional, and local policy measures or technology and market developments.…”
Section: Introductionmentioning
confidence: 99%